2020
DOI: 10.7759/cureus.8207
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) in Children: Vulnerable or Spared? A Systematic Review

Abstract: The ongoing pandemic of coronavirus disease 2019 (COVID-19) has affected people from all cultures, religions, gender, and age groups around the world. In the last few months, several studies have been conducted on various aspects of COVID-19. Our goal was to see if the pediatric population is vulnerable to this infection. In this review, we conducted extensive research mainly by using the PubMed database. We used Medical Subject Headings (MeSH) and associated keywords to engage in an extensive search focussing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
1
27
0
4
Order By: Relevance
“…It has been suggested that children with infections are less likely to have a cytokine storm caused by an excessive immune response, so leukopenia and lymphocyte decreases are relatively rare. Similarly, in the detection of Creactive protein, only 3 of 134 patients had transient increases in C-reactive protein (23,27, and 47 mg/L) (13).…”
Section: Family Clusters May Be the Most Important Clue For The Diagnmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that children with infections are less likely to have a cytokine storm caused by an excessive immune response, so leukopenia and lymphocyte decreases are relatively rare. Similarly, in the detection of Creactive protein, only 3 of 134 patients had transient increases in C-reactive protein (23,27, and 47 mg/L) (13).…”
Section: Family Clusters May Be the Most Important Clue For The Diagnmentioning
confidence: 99%
“…(1) Patients with underlying diseases such as congenital cardiopulmonary airway disease, chronic heart and kidney disease, malnutrition, cancer, diabetes, immune deficiency, hypothyroidism, genetic metabolic diseases, etc. (23,24). (2) Patients with long-term use of immunosuppressants (25).…”
Section: Clinical Early Warning Index Of Severe and Critical Infectiomentioning
confidence: 99%
“…Chest X-ray show infiltrates. CT scan is accurate and specific by showing ground glass opacities and sub segmental consolidation [34] The standards for diagnosis is made by the detection of the viral RNA by real time polymerase chain reaction from a nasopharngeal swab or sputum sample [14].…”
Section: Diagnosismentioning
confidence: 99%
“…[16] Throat swabs are relatively invasive, induce coughing and cause bleeding. Occasionally may increase the risk for health care workers [34]. Two consecutive negative RT-PCR to be obtained before discharge [15].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation